Acid and alkali resistant antistatic adhesive, and preparation method and application thereof
By using acid-base-resistant anti-static adhesives containing double-bonded amide monomers, double-bonded silane monomers, fluorine-containing acrylate monomers and aamide multi-walled carbon nanotubes in the PET protective film, the problem that the existing PET protective film is not resistant to acid-base and electrostatic pollution in an acid-base environment is solved, and a protective film with high acid-base resistance and anti-static properties is achieved.
Patent Information
- Application Number
- CN202411368701.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-03-04
AI Technical Summary
The existing PET protective film does not have acid-base resistance in acid-base environments, and is prone to static electricity during the peeling process, resulting in dust adsorption and glass surface contamination.
An acid-base-resistant anti-static adhesive is used, and the adhesive is added with double-bonded amide monomer, double-bonded silane monomer, fluorine-containing acrylate monomer and aamide multi-walled carbon nanotubes. Through the combination of these monomers and nanotubes, the acid-base-resistant and anti-static properties of the protective film are improved.
It significantly improves the acid and alkali resistance and anti-static properties of the protective film, ensures that it is not prone to corrosion in an acid-base environment, and prevents static electricity during the peeling process, reducing dust adsorption and pollution.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to an acid- and alkali-resistant antistatic adhesive, a preparation method and application thereof, and belongs to the technical field of optical protective films. Background Art
[0002] During the processing of electronic products, a protective film is usually applied to prevent them from being scratched or corroded in acidic or alkaline environments. Polyethylene terephthalate (PET) protective film has excellent optical properties and strength, and is widely used for surface protection of smartphone glass panels. During the production and manufacturing process of mobile phone glass panels, they need to be treated with strong acids and alkalis, requiring PET protective film to be acid- and alkali-resistant. When the protective film is torn off the glass surface, static electricity is easily generated, causing dust adsorption and contamination of the glass surface, requiring the protective film to have anti-static properties.
[0003] Chinese patent CN202011405016.2 discloses a PET acid-resistant and alkali-resistant protective film and a preparation method thereof, wherein the protective film is made of the following raw materials: PET, PE, LLDPE, plasticizer, antifogging agent, nano-silica, and the antifogging agent is made of the following raw materials: alkanolamide, glyceryl monostearate, vinyl bisstearamide, cellulose, N-(2-hydroxyethyl) dodecylamide. The protective film has good antifogging effect and good self-adhesive effect, and due to the high cross-linking of the composition, the molecular chains are closely arranged, the structure is dense, and the acid and alkali resistance is good, but the protective film does not have antistatic properties. Chinese patent CN202010468406.8 discloses a method for manufacturing an antistatic surface protective film and an antistatic surface protective film, providing an antistatic surface protective film that has a balanced adhesion at a low peeling speed and a high peeling speed, and can seek to take into account both antistatic and anti-pollution properties, but the protective film does not have acid and alkali resistance. Summary of the invention
[0004] The present invention is to overcome the drawbacks of the prior art and provide an acid-base resistant antistatic adhesive, a preparation method and an application thereof. Double-bond amide monomers, double-bond silane monomers and fluorine-containing acrylate monomers are added to the adhesive to greatly improve the acid-base resistance of the protective film. Aminated multi-walled carbon nanotubes are added to prepare a protective film with excellent antistatic properties. The resistance of the adhesive layer of the prepared antistatic protective film is within 1×10 9 Ω or less.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] An acid-base resistant antistatic adhesive, the adhesive comprising the following components in parts by weight:
[0007] Acrylate soft monomer 10-20 parts
[0008] Acrylate hard monomer 5-10 parts
[0009] Contains 1-3 parts of double bond amide monomer
[0010] 0.5-1.5 parts of double bond silane monomer
[0011] 1-4 parts of fluorinated acrylate monomer
[0012] 1-3 parts of amino-modified multi-walled carbon nanotubes
[0013] Initiator 0.5-1 part
[0014] Solvent 60-160 parts
[0015] 1-5 parts of blocked isocyanate.
[0016] In the above acid-base resistant antistatic adhesive, the acrylic soft monomer is one of butylene acrylate and isooctyl acrylate or two of them in any weight ratio; the acrylic hard monomer is one of methyl acrylate and ethyl methacrylate or two of them in any weight ratio.
[0017] In the above-mentioned acid-base resistant antistatic adhesive, the double-bond amide monomer is one of nicotinic acid amide and [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt or two of them in any weight ratio; the double-bond silane monomer is one of triallylsilane and tetraallylsilane or two of them in any weight ratio.
[0018] In the above acid-base resistant antistatic adhesive, the fluorine-containing acrylate monomer is one of methyl trifluoroacrylate and perfluorobutyl acrylate or both of them in any weight ratio.
[0019] In the above acid-base resistant antistatic adhesive, the amino multi-walled carbon nanotubes are amino multi-walled carbon nanotubes with a diameter of 20 nm and a length of 1 μm.
[0020] In the above acid-base resistant antistatic adhesive, the initiator is one of azobisisobutyronitrile and dibenzoyl peroxide or two of them in any weight ratio; the solvent is one of ethyl acetate and butyl acetate or two of them in any weight ratio.
[0021] A method for preparing an acid- and alkali-resistant antistatic adhesive, the preparation method comprising the following steps:
[0022] a. According to weight proportions, 10-20 parts of acrylate soft monomer, 5-10 parts of acrylate hard monomer, 1-3 parts of double bond amide monomer, 0.5-1.5 parts of double bond silane monomer, and 1-4 parts of fluorine-containing acrylate monomer are weighed and mixed evenly to obtain a mixed monomer;
[0023] b. Weigh 25%-45% of the mixed monomers and add them to the reactor, add 60-160 parts of the solvent to the reactor, stir evenly, heat to 75-85°C, weigh 0.5-1 part of the initiator and add it to the reactor, react for 0.5-1.5h, then add the remaining mixed monomers to the reactor, control the addition to be completed within 0.5-1.5h, and keep the temperature for reaction for 1-3h after the addition is completed;
[0024] c. After the reaction is completed, the temperature is lowered to 30-40°C, and 1-3 parts of amino-modified multi-walled carbon nanotubes and 1-5 parts of blocked isocyanate are added to obtain an adhesive for acid- and alkali-resistant antistatic protective film.
[0025] An application of an acid-base resistant antistatic adhesive, wherein the acid-base resistant antistatic adhesive is used on an antistatic protective film, the acid-base resistant antistatic adhesive is evenly coated on one side of the protective film, and a release film is attached to the adhesive layer.
[0026] In the application of the above acid-base resistant antistatic adhesive, the thickness of the adhesive layer is 8-12 μm.
[0027] The beneficial effects of the present invention are:
[0028] 1. The double-bond amide monomer introduced into the adhesive for the acid- and alkali-resistant antistatic protective film prepared by the present invention has antistatic properties, which provides the protective film with excellent antistatic properties. After curing, the amide group reacts with the isocyanate group to form a cross-linked network structure, which is beneficial to improving the acid and alkali resistance of the protective film.
[0029] 2. The adhesive for the acid- and alkali-resistant antistatic protective film prepared by the present invention introduces a double-bond silane monomer with excellent corrosion resistance and has strong surface tension and polarity, which is beneficial to improving the acid- and alkali-resistant performance of the protective film.
[0030] 3. Fluorine-containing acrylate monomers are introduced into the adhesive for the acid- and alkali-resistant antistatic protective film prepared by the present invention, and methyl trifluoroacrylate and perfluorobutyl acrylate with more fluorine-containing functional groups are selected. Fluorine itself has excellent corrosion resistance. Introducing it into the molecular chain of the adhesive can greatly improve the acid and alkali resistance of the prepared protective film.
[0031] 4. Aminated multi-walled carbon nanotubes are added to the adhesive for the acid- and alkali-resistant antistatic protective film prepared by the present invention. The amino groups on the surface of the carbon nanotubes react with the isocyanate groups during curing, which can provide the protective film with excellent antistatic properties. Through chemical reactions, the precipitation of antistatic agents can be effectively prevented.
[0032] 5. The adhesive for the acid- and alkali-resistant antistatic protective film prepared by the present invention does not require a curing agent to be added during use and can be directly coated on a machine, thereby reducing the glue preparation process.
[0033] 6. The resistance of the antistatic protective film prepared by the present invention is 1*10 9 Ω or less, when the adhesive layer of the protective film is attached to the glass surface, it is soaked in 5% sodium hydroxide aqueous solution for 24 hours and 5% sulfuric acid aqueous solution for 24 hours respectively. The protective film is tightly attached to the glass surface without bubble bulging or fogging. After the protective film is removed, there is no residual glue, dark shadow and other defects. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme of the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0035] The present invention provides an adhesive for an acid- and alkali-resistant antistatic protective film, comprising the following components: an acrylate soft monomer, an acrylate hard monomer, a double-bond amide monomer, a double-bond silane monomer, a fluorinated acrylate monomer, an amino multi-walled carbon nanotube, an initiator, a solvent, and a blocked isocyanate. The adhesive introduces a double-bond amide monomer, a double-bond silane monomer, and a fluorinated acrylate monomer, which greatly improves the acid- and alkali-resistant performance of the protective film. The amino multi-walled carbon nanotube is added, so that the prepared protective film has excellent antistatic performance. The resistance of the adhesive layer of the prepared antistatic protective film is 1*10 9 Ω or less, when the adhesive layer of the protective film is attached to the glass surface, it is immersed in 5% sodium hydroxide aqueous solution for 24 hours and 5% sulfuric acid aqueous solution for 24 hours respectively. The protective film is tightly attached to the glass surface without bubble bulging or fogging. After the protective film is removed, there is no residual glue, ghosting and other defects.
[0036] In order to obtain an adhesive with the desired performance, the present invention further restricts the components of the adhesive, in detail: the adhesive includes the following substances in parts by weight: 10-20 parts of acrylate soft monomer, 5-10 parts of acrylate hard monomer, 1-3 parts of double-bond amide monomer, 0.5-1.5 parts of double-bond silane monomer, 1-4 parts of fluorine-containing acrylate monomer, 1-3 parts of amino multi-walled carbon nanotubes, 0.5-1 parts of initiator, 60-160 parts of solvent, and 1-5 parts of blocked isocyanate.
[0037] Furthermore, in order to protect the peeling force stability of the film, the acrylic soft monomer is one of butyl acrylate and isooctyl acrylate or two of them in any weight ratio; the acrylic hard monomer is one of methyl acrylate and ethyl methacrylate or two of them in any weight ratio.
[0038] Furthermore, in order to improve the acid and alkali resistance, the double bond amide monomer is one of nicotinic acid amide, [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, or two of them in any weight ratio; the double bond silane monomer is one of triallylsilane and tetraallylsilane, or two of them in any weight ratio; the fluorine-containing acrylate monomer is one of methyl trifluoroacrylate and perfluorobutyl acrylate, or two of them in any weight ratio.
[0039] Furthermore, in order to improve the stability of the adhesive, the initiator is one of azobisisobutyronitrile and dibenzoyl peroxide or two of them in any weight ratio; the solvent is one of ethyl acetate and butyl acetate or two of them in any weight ratio.
[0040] The amino-modified multi-walled carbon nanotubes of the present invention are amino-modified multi-walled carbon nanotubes with a diameter of 20 nm and a length of 1 μm.
[0041] The blocked isocyanate of the present invention is selected from the following commercially available substances but is not limited thereto: one or any combination of BI7981 (LANXESS, Germany), BI7951 (LANXESS, Germany), HI100 (BASF, Germany), and B1358A (Evonik Degussa) can be selected.
[0042] Another object of the present invention is to provide a method for preparing an adhesive for an acid- and alkali-resistant antistatic protective film, wherein the adhesive is prepared by the following steps: the adhesive is prepared by the following steps: according to the weight proportions, 10-20 parts of acrylate soft monomer, 5-10 parts of acrylate hard monomer, 1-3 parts of double-bond amide monomer, 0.5-1.5 parts of double-bond silane monomer, and 1-4 parts of fluorine-containing acrylate monomer are weighed and mixed evenly to obtain a mixed monomer; 25%-45% of the mixed monomer is weighed and added to a reactor, 60-160 parts of a solvent is added to the reactor, stirred evenly, heated to 75-85°C, 0.5-1 parts of an initiator is weighed and added to the reactor, reacted for 0.5-1.5h, and then the remaining mixed monomer is added to the reactor, the addition is controlled to be completed within 0.5-1.5h, and the reaction is kept warm for 1-3h after the addition is completed. After the reaction is completed, the temperature is lowered to 30-40°C, and 1-3 parts of amino multi-walled carbon nanotubes and 1-5 parts of blocked isocyanate are added to obtain an adhesive for acid- and alkali-resistant antistatic protective film. The method provided by the present invention achieves the technical effect of preparing an adhesive having acid- and alkali-resistant properties and antistatic properties by controlling the addition order, heating time and temperature. The present invention can effectively control the structure of the molecular chain by adding mixed monomers in batches, so that different monomers are evenly distributed in the polymer segment, and the prepared adhesive has a more stable peeling force.
[0043] The adhesive is applied in this application, mainly for antistatic protective film. When applied, one side of the antistatic protective film is coated with the adhesive for acid- and alkali-resistant antistatic protective film, and a layer of release film is attached to the adhesive layer. The protective film substrate of the present invention is a 50μm optical grade PET polyester film. Preferably, the thickness of the adhesive layer of the present invention is 8-12μm, because the peeling force is controlled and the adhesion performance between the adhesive layer and the polyester film is increased.
[0044] The present invention is further described in detail below in conjunction with specific implementation modes, but the implementation of the present invention is not limited thereto.
[0045] Example 1
[0046] (1) According to weight proportions, 5 g of butylene glycol acrylate, 5 g of isooctyl acrylate, 7.5 g of methyl acrylate, 1 g of nicotinamide, 1 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 1 g of triallylsilane, 1.5 g of methyl trifluoroacrylate, and 1.5 g of perfluorobutyl acrylate were weighed and mixed uniformly to obtain a mixed monomer.
[0047] (2) Weigh 5.88 g of the mixed monomer and add it to the reactor, add 50 g of ethyl acetate and 80 g of butyl acetate to the reactor, stir evenly, heat to 80° C., weigh 1 g of azobisisobutyronitrile and add it to the reactor, react for 1 hour, and then add the remaining mixed monomer to the reactor, control the addition to be completed within 1 hour, and keep the temperature for reaction for 2 hours after the addition is completed.
[0048] (3) After the reaction is completed, the temperature is lowered to 35° C., and 2 g of amino-modified multi-walled carbon nanotubes, 0.5 g of BI7981 (Lanxess, Germany), 0.5 g of BI7951 (Lanxess, Germany), 1 g of HI100 (BASF, Germany), and 0.5 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0049] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 9 μm. The evaluation results are listed in Table 1.
[0050] Example 2
[0051] (1) According to weight proportions, 15 g of isooctyl acrylate, 2 g of methyl acrylate, 3 g of ethyl methacrylate, 3 g of nicotinamide, 0.75 g of triallylsilane, 2 g of methyl trifluoroacrylate, and 2 g of perfluorobutyl acrylate were weighed and mixed uniformly to obtain a mixed monomer.
[0052] (2) Weigh 9.71 g of the mixed monomer and add it to the reactor, add 110 g of ethyl acetate to the reactor, stir evenly, heat to 75° C., weigh 0.3 g of azobisisobutyronitrile and 0.3 g of dibenzoyl peroxide and add them to the reactor, react for 0.5 h, and then add the remaining mixed monomer to the reactor, control the addition to be completed within 0.75 h, and keep the reaction warm for 1 h after the addition is completed.
[0053] (3) After the reaction is completed, the temperature is lowered to 40° C., and 1.5 g of amino-modified multi-walled carbon nanotubes, 1 g of BI7981 (Lanxess, Germany), 1 g of BI7951 (Lanxess, Germany), and 1 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0054] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 10 μm. The evaluation results are listed in Table 1.
[0055] Example 3
[0056] (1) According to weight proportions, 5 g of butylene glycol acrylate, 7.5 g of isooctyl acrylate, 9 g of ethyl methacrylate, 1.5 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 0.2 g of triallylsilane, 0.3 g of tetraallylsilane, and 2.5 g of perfluorobutyl acrylate were weighed and mixed uniformly to obtain a mixed monomer.
[0057] (2) Weigh 7.8 g of the mixed monomers and add them to the reactor, add 80 g of ethyl acetate and 80 g of butyl acetate to the reactor, stir evenly, heat to 82° C., weigh 0.8 g of dibenzoyl peroxide and add it to the reactor, react for 0.75 h, and then add the remaining mixed monomers to the reactor, control the addition to be completed within 1.5 h, and keep the reaction warm for 2.5 h after the addition is completed.
[0058] (3) After the reaction is completed, the temperature is lowered to 30° C., and 2.5 g of amino-modified multi-walled carbon nanotubes, 0.5 g of BI7981 (Lanxess, Germany), and 0.5 g of BI7951 (Lanxess, Germany) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0059] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 12 μm. The evaluation results are listed in Table 1.
[0060] Example 4
[0061] (1) According to weight proportions, 20 g of isooctyl acrylate, 5 g of methyl acrylate, 5 g of ethyl methacrylate, 0.5 g of nicotinamide, 0.5 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 1.25 g of triallylsilane, 1 g of methyl trifluoroacrylate, and 2 g of perfluorobutyl acrylate were weighed and mixed uniformly to obtain a mixed monomer.
[0062] (2) Weigh 15.86 g of the mixed monomers and add them to the reactor, add 60 g of butyl acetate to the reactor, stir evenly, heat to 85° C., weigh 0.2 g of azobisisobutyronitrile and 0.3 g of dibenzoyl peroxide and add them to the reactor, react for 1.5 h, and then add the remaining mixed monomers to the reactor, control the addition to be completed within 0.5 h, and keep the reaction warm for 1.5 h after the addition is completed.
[0063] (3) After the reaction is completed, the temperature is lowered to 32° C., and 3 g of amino-modified multi-walled carbon nanotubes, 1 g of BI7981 (Lanxess, Germany), 1.5 g of BI7951 (Lanxess, Germany), 1.5 g of HI100 (BASF, Germany), and 1 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0064] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 11 μm. The evaluation results are listed in Table 1.
[0065] Example 5
[0066] According to weight proportions, 10 g of butylene acrylate, 7.5 g of isooctyl acrylate, 8 g of methyl acrylate, 2.5 g of nicotinamide, 0.5 g of triallylsilane, 1 g of tetraallylsilane, and 1 g of perfluorobutyl acrylate were weighed and mixed evenly to obtain a mixed monomer.
[0067] (2) Weigh 12.2 g of the mixed monomers and add them to the reactor. Add 75 g of ethyl acetate and 75 g of butyl acetate to the reactor, stir evenly, heat to 77° C., weigh 0.7 g of dibenzoyl peroxide and add it to the reactor. React for 1.25 h, then add the remaining mixed monomers to the reactor. Add the mixture within 1.25 h. After the addition is complete, keep the mixture warm for 3 h.
[0068] (3) After the reaction is completed, the temperature is lowered to 37° C., and 1 g of amino-modified multi-walled carbon nanotubes, 2 g of BI7981 (Lanxess, Germany), and 2 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0069] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 8 μm. The evaluation results are listed in Table 1.
[0070] Comparative Example 1, different from Example 1
[0071] (1) According to weight proportions, 5 g of butyl acrylate, 5 g of isooctyl acrylate, 7.5 g of methyl acrylate, and 1.5 g of perfluorobutyl acrylate were weighed and mixed uniformly to obtain a mixed monomer.
[0072] (2) Weigh 4.75 g of the mixed monomer and add it to the reactor, add 50 g of ethyl acetate and 80 g of butyl acetate to the reactor, stir evenly, heat to 80° C., weigh 1 g of azobisisobutyronitrile and add it to the reactor, react for 1 hour, and then add the remaining mixed monomer to the reactor, control the addition to be completed within 1 hour, and keep the temperature for reaction for 2 hours after the addition is completed.
[0073] (3) After the reaction is completed, the temperature is lowered to 35° C., and 2 g of amino-modified multi-walled carbon nanotubes, 0.5 g of BI7981 (Lanxess, Germany), 0.5 g of BI7951 (Lanxess, Germany), 1 g of HI100 (BASF, Germany), and 0.5 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0074] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 9 μm. The evaluation results are listed in Table 1.
[0075] Comparative Example 2, different from Example 2
[0076] (1) According to weight parts, 15 g of isooctyl acrylate, 2 g of methyl acrylate, 3 g of ethyl methacrylate, and 3 g of nicotinamide were weighed and mixed evenly to obtain a mixed monomer.
[0077] (2) Weigh 8.05 g of the mixed monomers and add them to the reactor, add 110 g of ethyl acetate to the reactor, stir evenly, heat to 75° C., weigh 0.3 g of azobisisobutyronitrile and 0.3 g of dibenzoyl peroxide and add them to the reactor, react for 0.5 h, and then add the remaining mixed monomers to the reactor, control the addition to be completed within 0.75 h, and keep the temperature for reaction for 1 h after the addition is completed.
[0078] (3) After the reaction is completed, the temperature is lowered to 40° C., and 1 g BI7981 (Lanxess, Germany), 1 g BI7951 (Lanxess, Germany), and 1 g B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0079] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 10 μm. The evaluation results are listed in Table 1.
[0080] Comparative Example 3, different from Example 3
[0081] (1) According to weight proportions, 5 g of butylene glycol acrylate, 7.5 g of isooctyl acrylate, 9 g of ethyl methacrylate, and 0.2 g of triallylsilane were weighed and mixed uniformly to obtain a mixed monomer.
[0082] (2) Weigh 6.51 g of the mixed monomer and add it to the reactor, add 80 g of ethyl acetate and 80 g of butyl acetate to the reactor, stir evenly, heat to 82° C., weigh 0.8 g of dibenzoyl peroxide and add it to the reactor, react for 0.75 h, and then add the remaining mixed monomer to the reactor, control the addition to be completed within 1.5 h, and keep the reaction warm for 2.5 h after the addition is completed.
[0083] (3) After the reaction is completed, the temperature is lowered to 30° C., and 2.5 g of amino-modified multi-walled carbon nanotubes, 0.5 g of BI7981 (Lanxess, Germany), and 0.5 g of BI7951 (Lanxess, Germany) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0084] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 12 μm. The evaluation results are listed in Table 1.
[0085] Comparative Example 4 is different from Example 4
[0086] (1) According to weight proportions, 20 g of isooctyl acrylate, 5 g of methyl acrylate, 5 g of ethyl methacrylate, 0.5 g of nicotinamide, 0.5 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 1 g of methyl trifluoroacrylate, and 2 g of perfluorobutyl acrylate were weighed and mixed uniformly to obtain a mixed monomer.
[0087] (2) Weigh 15.3 g of the mixed monomers and add them to the reactor, add 60 g of butyl acetate to the reactor, stir evenly, heat to 85° C., weigh 0.2 g of azobisisobutyronitrile and 0.3 g of dibenzoyl peroxide and add them to the reactor, react for 1.5 h, and then add the remaining mixed monomers to the reactor, control the addition to be completed within 0.5 h, and keep the temperature for reaction for 1.5 h after the addition is completed.
[0088] (3) After the reaction is completed, the temperature is lowered to 32° C., and 3 g of amino-modified multi-walled carbon nanotubes, 1 g of BI7981 (Lanxess, Germany), 1.5 g of BI7951 (Lanxess, Germany), 1.5 g of HI100 (BASF, Germany), and 1 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0089] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 11 μm. The evaluation results are listed in Table 1.
[0090] Comparative Example 5, different from Example 5
[0091] According to weight proportions, 10 g of butylene glycol acrylate, 7.5 g of isooctyl acrylate, 8 g of methyl acrylate, 2.5 g of nicotinamide, 0.5 g of triallylsilane, and 1 g of tetraallylsilane were weighed and mixed uniformly to obtain a mixed monomer.
[0092] (2) Weigh 11.8 g of the mixed monomers and add them to the reactor. Add 75 g of ethyl acetate and 75 g of butyl acetate to the reactor, stir evenly, heat to 77° C., weigh 0.7 g of dibenzoyl peroxide and add it to the reactor. React for 1.25 h, then add the remaining mixed monomers to the reactor. Add the mixture within 1.25 h. After the addition is completed, keep the mixture warm for 3 h.
[0093] (3) After the reaction is completed, the temperature is lowered to 37° C., and 1 g of amino-modified multi-walled carbon nanotubes, 2 g of BI7981 (Lanxess, Germany), and 2 g of B1358A (Evonik Degussa) are added to obtain an adhesive for an acid- and alkali-resistant antistatic protective film.
[0094] The adhesive was coated on the surface of a 50 μm thick optical grade PET polyester film, the polyester film was placed in an oven at 110°C for 1 min, the polyester film was taken out, and a release film was applied on the adhesive layer surface to obtain an antistatic protective film with an adhesive layer thickness of 8 μm. The evaluation results are listed in Table 1.
[0095] The test methods for each performance in the table are as follows:
[0096] (1) Peel force test
[0097] Cut the protective film into a size of 300*25mm, tear off the release film, and stick the protective film on the surface of the polarizer. Use an electronic universal testing machine (model: AGS-X) to perform a peeling test at an angle of 180° and a tensile speed of 300mm / min.
[0098] (2) Glue layer resistance test
[0099] Cut the protective film into 12*12mm size, tear off the release film, and test the surface resistance of the film on a high resistance meter (model: SME-8310).
[0100] (3) Acid resistance
[0101] Cut the protective film into a size of 150*25mm, tear off the release film, stick the protective film adhesive layer on the glass surface, and soak it in a 5%wt sulfuric acid aqueous solution for 24 hours. After taking out the sample, observe whether the protective film on the glass surface has wrinkles, detachment, or bubbles. After tearing off the protective film, observe whether there is residual glue or ghosting on the glass surface. If not, it is judged as qualified. If so, it is judged as unqualified.
[0102] (4) Alkali resistance
[0103] Cut the protective film into a size of 150*25mm, tear off the release film, stick the protective film adhesive layer on the glass surface, and soak it in a 5%wt sodium hydroxide aqueous solution for 24 hours. After taking out the sample, observe whether the protective film on the glass surface has wrinkles, detachment, or bubbles. After tearing off the protective film, observe whether there is residual glue or ghosting on the glass surface. If not, it is judged as qualified. If so, it is judged as unqualified.
[0104] Table 1 Performance data table
[0105]
[0106] As can be seen from the table, in Example 1, 1g of nicotinic acid amide, 1g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, and 1g of triallylsilane are added. Nicotinic acid amide and [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt are amide monomers containing double bonds, and triallylsilane is a silane monomer containing double bonds. In Comparative Example 1, only perfluorobutyl acrylate (fluorinated acrylate monomer) is added, and no amide monomer containing double bonds and no silane monomer containing double bonds are added. The simultaneous addition of the above three monomers can improve the acid and alkali resistance of the protective film.
[0107] In Example 2, 0.75 g of triallylsilane, 2 g of methyl trifluoroacrylate, 2 g of perfluorobutyl acrylate, and 1.5 g of amino-modified multi-walled carbon nanotubes were added. In Comparative Example 2, only nicotinic acid amide (double-bond amide monomer) was added, and double-bond silane monomer and fluorinated acrylate monomer were not added. This indicates that only when double-bond amide monomer, double-bond silane monomer, and fluorinated acrylate monomer are added simultaneously can the acid and alkali resistance of the protective film be improved. In addition, the adhesive layer resistance of Comparative Example 2 is greater than 1*10 12 Ω, far exceeding the resistance of the glue layer in the embodiment 25.21*10 7 Ω, indicating that multi-walled carbon nanotubes can reduce the resistance of the protective film.
[0108] In Example 3, 1.5g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 0.2g of triallylsilane, 0.3g of tetraallylsilane, and 2.5g of perfluorobutyl acrylate were added. In Comparative Example 3, only 0.2g of triallylsilane was added, and no double-bond-containing amide monomer and fluorine-containing acrylate monomer were added. The acid and alkali resistance of the protective film was unqualified, indicating that the acid and alkali resistance of the protective film can only be improved after the double-bond-containing amide monomer, the double-bond-containing silane monomer and the fluorine-containing acrylate monomer are added at the same time.
[0109] In Example 4, 0.5 g of nicotinamide, 0.5 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 1.25 g of triallylsilane, 1 g of methyl trifluoroacrylate, and 2 g of perfluorobutyl acrylate were added. In Comparative Example 4, 0.5 g of nicotinamide, 0.5 g of [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt, 1 g of methyl trifluoroacrylate, and 2 g of perfluorobutyl acrylate were added, but triallylsilane was not added, resulting in an increasing trend in the peeling force and a decrease in the acid and alkali resistance. This indicates that only by simultaneously introducing the double-bond amide monomer, the double-bond silane monomer, and the fluorine-containing acrylate monomer into the polymer chain can the acid and alkali resistance of the protective film be greatly improved.
[0110] In Example 5, 2.5 g of nicotinamide, 0.5 g of triallylsilane, 1 g of tetraallylsilane, and 1 g of perfluorobutyl acrylate were added, and in Comparative Example 5, 2.5 g of nicotinamide, 0.5 g of triallylsilane, and 1 g of tetraallylsilane were added, but perfluorobutyl acrylate was not added, resulting in unqualified acid and alkali resistance of the protective film. This indicates that only by simultaneously introducing double-bond amide monomers, double-bond silane monomers, and fluorine-containing acrylate monomers into the polymer chain can the acid and alkali resistance of the protective film be greatly improved.
[0111] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. An acid and alkali resistant antistatic adhesive, characterized in that: The adhesive comprises the following components in parts by weight: Acrylate soft monomer 10-20 parts Acrylate hard monomer 5-10 parts Contains 1-3 parts of double bond amide monomer 0.5-1.5 parts of double bond silane monomer 1-4 parts of fluorinated acrylate monomer 1-3 parts of amino-modified multi-walled carbon nanotubes Initiator 0.5-1 part Solvent 60-160 parts 1-5 parts of blocked isocyanate.
2. The acid and alkali resistant antistatic adhesive according to claim 1, characterized in that: The acrylic acid ester soft monomer is one of butylene glycol acrylate and isooctyl acrylate or two of them in any weight ratio; the acrylic acid ester hard monomer is one of methyl acrylate and ethyl methacrylate or two of them in any weight ratio.
3. The acid and alkali resistant antistatic adhesive according to claim 1, characterized in that: The double bond-containing amide monomer is one of nicotinic acid amide and [3-(methacrylamido)propyl]dimethyl(3-thiopropyl)ammonium hydroxide inner salt or two of them in any weight ratio; the double bond-containing silane monomer is one of triallylsilane and tetraallylsilane or two of them in any weight ratio.
4. The acid- and alkali-resistant antistatic adhesive according to claim 1, characterized in that: The fluorine-containing acrylate monomer is one of methyl trifluoroacrylate and perfluorobutyl acrylate or two of them in any weight ratio.
5. The acid and alkali resistant antistatic adhesive according to claim 1, characterized in that: The amino-modified multi-walled carbon nanotubes are amino-modified multi-walled carbon nanotubes with a diameter of 20 nm and a length of 1 μm.
6. The acid- and alkali-resistant antistatic adhesive according to claim 1, characterized in that: The initiator is one of azobisisobutyronitrile and dibenzoyl peroxide or two of them in any weight ratio; the solvent is one of ethyl acetate and butyl acetate or two of them in any weight ratio.
7. A method for preparing the acid-base resistant antistatic adhesive according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: a. According to weight proportions, 10-20 parts of acrylate soft monomer, 5-10 parts of acrylate hard monomer, 1-3 parts of double bond amide monomer, 0.5-1.5 parts of double bond silane monomer, and 1-4 parts of fluorine-containing acrylate monomer are weighed and mixed evenly to obtain a mixed monomer; b. Weigh 25%-45% of the mixed monomers and add them to the reactor, add 60-160 parts of the solvent to the reactor, stir evenly, heat to 75-85°C, weigh 0.5-1 part of the initiator and add it to the reactor, react for 0.5-1.5h, then add the remaining mixed monomers to the reactor, control the addition to be completed within 0.5-1.5h, and keep the temperature for reaction for 1-3h after the addition is completed; c. After the reaction is completed, the temperature is lowered to 30-40°C, and 1-3 parts of amino-modified multi-walled carbon nanotubes and 1-5 parts of blocked isocyanate are added to obtain an adhesive for acid- and alkali-resistant antistatic protective film.
8. An application of the acid-base resistant antistatic adhesive according to any one of claims 1 to 6, characterized in that: The acid-base resistant antistatic adhesive is used on the antistatic protective film. The acid-base resistant antistatic adhesive is evenly coated on one side of the protective film, and a release film is attached to the adhesive layer.
9. The use of the acid-base resistant antistatic adhesive according to claim 8, characterized in that: The thickness of the adhesive layer is 8-12 μm.
Citation Information
Patent Citations
Method for producing antistatic surface protective film, and antistatic surface protective film
CN112126372A
PET acid and alkali resistant protective film and preparation method thereof
CN112521731A